A Statistical Analysis of Stock Performance Linking the Pandemic/Epidemic Outbreaks from 2010 till 2020: A Profound Look into the U.S Stock Market - Promy, Farhana Jahan (2020)
The paper analyses the stock performance during the pandemic outbreaks from 2010 till 2020, particularly concentrating in the U.S. stock market. The key focus of this dissertation is to highlight the implications of behavioural finance and investments. In order to do this, stock performances are analysed through "fear index", also known as VIX and Daily treasure yield curve rate. Panel data analysis is conducted on the 5 major stock indexes to provide an overall glimpse of the U.S. economy. No primary research (such as Interviews, Surveys etc.) had been conducted to fulfil the study. The paper incorporates both qualitative and quantitative analysis. Quantitative analysis focuses on the three panel data models to determine the statistical significance of the variables, with an additional test to determine the most efficient model. The qualitative part conducts a thorough analysis on the medicine sector, particularly the pharmaceutical industries during epidemic times. Overall, the paper tried to illustrate the importance of market psychologies through various analysis.